Bionic osmotic pressure regulation type water system zinc ion battery anti-freezing electrolyte and application thereof

CN123018172APending Publication Date: 2026-10-30HENAN NORMAL UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610989646.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

以上两篇专利文献的技术方案并没有关于采用将生物体内天然产生的抗冻小分子作为外源添加剂引入硫酸锌水系电解液中,通过仿生学原理构建深共晶电解液打破并重构体相水分子的氢键网络,从而在不依赖高浓度有机主体共溶剂的前提下,构筑兼具极端低温防结冰与调控负极界面溶剂化壳层双重功能的水系电解液体系的相关记载和技术启示

Benefits of technology

[0026]优异的低温抗冻性能:仿生渗透压调节剂即生物源天然抗冻小分子调节剂含有丰富的极性基团(如羟基、氨基等),能够与水分子形成强烈的氢键相互作用,打破了纯水中原有的氢键网络,显著降低了自由水的活性,抑制了大尺寸冰晶的形核与生长,使得电解液在-20℃甚至更低温度下仍保持极高的离子电导率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018172A_ABST
    Figure CN123018172A_ABST
Patent Text Reader

Abstract

The application discloses a kind of bionic osmotic pressure regulation type water series zinc ion battery antifreeze electrolyte and its application, wherein antifreeze electrolyte includes zinc salt, water and biological source natural antifreeze small molecule regulator, regulator is selected from at least one in polyhydric alcohol, saccharide, amino acid and its derivative, betaine or amide, regulator is as hydrogen bond donor and hydrogen bond acceptor, constructs bionic solvation system with deep eutectic characteristics, destroys hydrogen bond network between water molecules, significantly reduces electrolyte freezing point;Regulator makes electrolyte still maintain very high ionic conductivity under low temperature environment, effectively inhibits zinc negative electrode dendrite growth and hydrogen evolution side reaction, substantially improves the cycle stability and coulomb efficiency of battery, realizes long-term stable cycle of water series zinc ion battery under low temperature environment.The electrolyte of the application is green and environmentally friendly, simple to prepare, solves the technical problems of fast low-temperature failure and short service life of water series zinc ion battery, and has wide prospect in the field of low-temperature energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aqueous zinc-ion battery technology, specifically relating to a biomimetic osmotic pressure-regulated aqueous zinc-ion battery antifreeze electrolyte and its application. Background Technology

[0002] With the rapid development of large-scale energy storage systems, aqueous zinc-ion batteries (AZIBs) have become one of the most competitive energy storage technologies due to their high safety, low cost, environmental friendliness, and extremely high theoretical capacity (820 mAh / g) of the zinc metal anode. However, the electrolyte of traditional aqueous zinc-ion batteries is mainly composed of water and zinc salts, and this electrolyte system faces severe challenges in practical applications.

[0003] Current conventional aqueous electrolytes face three major technical bottlenecks in complex environments, especially at low temperatures: First, aqueous electrolytes contain a large number of free water molecules with a high freezing point. At temperatures below 0°C, these water molecules readily combine to form large ice crystals, disrupting ion transport pathways and causing a sharp drop in ionic conductivity, rendering the battery inoperable. Second, the high reactivity of free water in aqueous electrolytes makes it prone to decomposition on the negative electrode surface during charging and discharging, generating hydrogen gas. This not only leads to electrolyte drying and battery swelling but also causes a localized increase in pH, inducing the formation of alkaline byproducts and accelerating the chemical corrosion of the zinc negative electrode. Third, during battery cycling, zinc ion deposition on the negative electrode surface is often uneven. The electrochemical environment driven by free water easily leads to rapid zinc accumulation at the tips, forming penetrating zinc dendrites that eventually pierce the separator, causing an internal short circuit.

[0004] To address the aforementioned technical challenges, existing technologies typically employ "salt-in-water" solutions, i.e., high-concentration electrolytes, or introduce organic co-solvents. However, high-concentration electrolytes are extremely expensive and have high viscosity and poor wettability; while commonly used organic solvents (such as acetonitrile) are often flammable or toxic, sacrificing the battery's inherent high safety advantage. We have discovered that many cold-resistant organisms in nature (such as polar fish and cold-resistant plants) can prevent their cells from freezing and cracking in extremely cold environments by secreting and accumulating specific osmotic pressure regulators (such as polyols, sugars, amino acids, and other small molecules). These biomolecules alter the physicochemical state of water molecules through strong interactions. How to draw upon this survival wisdom of nature and completely solve the low-temperature and interfacial stability problems of aqueous zinc-ion batteries through molecular-level synergistic regulation has become a key scientific problem urgently needing to be solved in this field.

[0005] The prior art patent document CN122025857A discloses an aqueous zinc battery electrolyte, its preparation method, and its application. The electrolyte is composed of zinc salt, water, and ionic liquid, with the ionic liquid accounting for no less than 50% of the mass. By using the ionic liquid as the main co-solvent to construct a ternary homogeneous system of zinc salt-water-ionic liquid, this electrolyte can effectively improve the solubility of conventional zinc salt in the system and significantly reduce water activity. It avoids side reactions such as hydrogen evolution and oxygen evolution caused by bulk water under high voltage conditions, as well as dendrite growth at the zinc anode interface. It improves the electrochemical stability window of the electrolyte and the reversibility of zinc deposition / dissolution, thereby improving the cycle life and high voltage energy density of the battery. Patent document CN121839921A discloses an electrolyte using sodium pyruvate as an additive and its application in zinc batteries. The electrolyte consists of sodium pyruvate, zinc sulfate, and deionized water. By introducing sodium pyruvate, the pyruvate anion replaces some water molecules in the original hydrated ions, altering the solvation structure of zinc ions and allowing them to preferentially occupy electrode active sites. This electrolyte accelerates zinc ion migration kinetics and promotes uniform zinc deposition, effectively inhibiting interfacial corrosion and dendrite growth, improving the stability and reversibility of the zinc anode during deposition / stripping, and thus enhancing the cycle life and practicality of aqueous zinc batteries. Neither of these patent documents contains any mention or technical inspiration regarding the use of naturally occurring antifreeze molecules as exogenous additives in aqueous electrolytes. Instead, they describe the construction of a deep eutectic electrolyte based on biomimetic principles to break and reconstruct the hydrogen bond network of bulk water molecules, thereby constructing an aqueous electrolyte system with dual functions of extreme low-temperature anti-icing and regulation of the negative electrode interface solvation shell without relying on a high-concentration organic co-solvent.

[0006] The prior art patent document CN121862903A discloses an aqueous zinc-ion battery electrolyte containing 1,3-dihydroxyacetone, its preparation method, and its application. The electrolyte includes zinc salt, deionized water, and 1,3-dihydroxyacetone as an additive. By ultrasonic mixing, the carbonyl and hydroxyl groups in the 1,3-dihydroxyacetone molecules preferentially coordinate with zinc ions into the solvation sheath layer and adsorb onto the zinc anode surface to regulate the interfacial double layer structure. This electrolyte can effectively reconstruct the solvation structure of zinc ions and construct a water-poor interfacial layer, replacing some active water molecules, improving ion diffusion and nucleation kinetics at the zinc interface, inhibiting hydrogen evolution, zinc foil corrosion, and zinc dendrite growth, and improving the stability and reversibility of the zinc anode during deposition / stripping, thereby enabling the aqueous zinc-ion battery to have long-cycle stability. Patent document CN122136494A discloses a modified electrolyte for aqueous zinc-ion batteries and its preparation method. The modified electrolyte includes a basic electrolyte and sulfur-defective molybdenum disulfide quantum dots as additives. By introducing quantum dot additives into the zinc sulfate basic electrolyte, the high specific surface area and high active site advantages of quantum dots, combined with the low zinc migration barrier and strong zinc affinity of sulfur-defective molybdenum disulfide, can form a dynamic adaptive interface adsorption layer on the surface of the battery negative electrode and accurately reconstruct the solvation structure of zinc ions. This electrolyte can improve the stability and reversibility of the zinc anode during the deposition / stripping process, thereby significantly improving the cycle life and specific capacity performance of the battery. The technical solutions in the two patent documents mentioned above do not contain any record or technical inspiration regarding the use of naturally occurring antifreeze molecules in biological bodies as exogenous additives to introduce zinc sulfate aqueous electrolytes, constructing deep eutectic electrolytes through biomimetic principles to break and reconstruct the hydrogen bond network of bulk water molecules, thereby constructing an aqueous electrolyte system with dual functions of extreme low-temperature anti-icing and regulation of the solvation shell of the negative electrode interface without relying on high-concentration organic co-solvents.

[0007] Therefore, developing a safe, efficient, broad-spectrum aqueous zinc-ion battery biomimetic electrolyte system that can balance antifreeze properties and a stable interface remains a critical technological bottleneck that needs to be overcome in this field. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the present invention aims to provide a biomimetic osmotic pressure-regulated aqueous zinc-ion battery antifreeze electrolyte and a zinc-iodine battery containing the antifreeze electrolyte. This invention aims to simultaneously solve three major problems—the easy freezing of aqueous electrolytes at low temperatures, severe dendrite formation and side reactions in the zinc anode, and the shuttle effect of polyiodide in the iodine-based cathode—through synergistic effects at the molecular level, thereby constructing an aqueous zinc-ion battery energy storage system with high energy density, long lifespan, and adaptability to extreme low-temperature environments.

[0009] To achieve the above objectives, the present invention adopts the following technical solution:

[0010] In a first aspect, the present invention provides a biomimetic osmotic pressure-regulated aqueous zinc-ion battery antifreeze electrolyte, wherein the antifreeze electrolyte comprises zinc salt, water, and a bio-derived natural antifreeze small molecule regulator, wherein the bio-derived natural antifreeze small molecule regulator has a mass percentage of 5% to 80% in the antifreeze electrolyte, and the bio-derived natural antifreeze small molecule regulator is selected from biocompatible small molecules with multiple hydrophilic groups, specifically selected from at least one of polyols, sugars, amino acids and their derivatives, betaines, or amides. This antifreeze electrolyte is used to assemble aqueous zinc-ion batteries suitable for low-temperature environments (≤-20℃), wherein the bio-derived natural antifreeze small molecule regulator… The regulator acts as a hydrogen bond donor and acceptor, constructing a biomimetic solvation system with deep eutectic properties. This disrupts the hydrogen bond network between water molecules, significantly lowering the electrolyte's freezing point. The bio-derived natural antifreeze small molecule regulator contains abundant polar groups that can form strong hydrogen bond interactions with water molecules, breaking the original hydrogen bond network in pure water. This significantly reduces the activity of free water, inhibits the nucleation and growth of large-sized ice crystals, and allows the electrolyte to maintain extremely high ionic conductivity even at low temperatures. This effectively inhibits dendrite growth and hydrogen evolution side reactions in the zinc anode, greatly improving the battery's cycle stability and coulombic efficiency, thereby achieving long-term stable cycling of aqueous zinc-ion batteries at low temperatures.

[0011] Preferably, the bio-derived natural antifreeze small molecule regulator is specifically selected from at least one of the following categories:

[0012] Polyols: at least one of glycerol, sorbitol or mannitol;

[0013] Sugars: at least one of trehalose, glucose, sucrose or fructose;

[0014] Amino acids and their derivatives: at least one of proline, alanine, aspartic acid, serine, valine, leucine, isoleucine, glutamine, or sarcosine;

[0015] Betaines: at least one of betaine or trimethylamine oxide;

[0016] Amides: Urea.

[0017] Preferably, the zinc salt is selected from at least one of zinc sulfate, zinc chloride, zinc acetate, zinc trifluoromethanesulfonate, or zinc perchlorate, and the molar concentration of the zinc salt in the antifreeze electrolyte is 0.5~4 mol / L.

[0018] Furthermore, the bio-derived natural antifreeze small molecule regulator is composed of components with different functional orientations. Through multi-site synergistic effects between different polar functional groups (such as hydroxyl, amino, and carboxyl groups), it can maintain high ionic conductivity while further enhancing the perturbation depth of the hydrogen bond network of bulk water molecules, and construct a more flexible dynamic adsorption protective layer at the solid-liquid interface. For example, by using polyols and amino acids and their derivatives for compound modification, the excellent low-temperature antifreeze properties of polyols can be organically combined with the strong chemical anchoring of polyiodides and the regulatory effect of amino acids and their derivatives on zinc nucleation behavior, synergistically achieving a second leap in battery electrochemical performance (such as capacity retention and rate performance).

[0019] Secondly, the present invention provides a zinc-iodine battery comprising the above-mentioned antifreeze electrolyte, wherein the zinc-iodine battery comprises a positive electrode, a negative electrode, a separator, and the above-mentioned biomimetic osmotic pressure regulating aqueous zinc-ion battery antifreeze electrolyte, and the zinc-iodine battery comprises a zinc-iodine button cell or a zinc-iodine pouch cell.

[0020] Preferably, the negative electrode is a zinc metal negative electrode or a zinc alloy negative electrode; the diaphragm is a glass fiber diaphragm, a cellulose diaphragm, or a polymer diaphragm.

[0021] Preferably, the positive electrode is an iodine-based composite positive electrode, which includes a conductive carbon host carrier and an active material loaded in the conductive carbon host carrier, wherein the active material is selected from at least one of elemental iodine or iodides.

[0022] More preferably, the conductive carbon host carrier is selected from at least one of porous carbon, carbon nanotubes, graphene, carbon fiber cloth, MXene, or conductive polymer; the active substance is stably adsorbed in the conductive carbon host carrier by at least one of physical confinement, chemical coordination anchoring, or electrostatic attraction.

[0023] Thirdly, the present invention provides a zinc-zinc battery comprising the above-mentioned antifreeze electrolyte, the zinc-zinc battery comprising a positive electrode, a negative electrode, a separator, and the above-mentioned biomimetic osmotic pressure regulating aqueous zinc-ion battery antifreeze electrolyte, the zinc-zinc battery being a zinc-zinc symmetric battery.

[0024] Preferably, the negative electrode is a zinc metal negative electrode or a zinc alloy negative electrode; the diaphragm is a glass fiber diaphragm, a cellulose diaphragm, or a polymer diaphragm; and the positive electrode is a zinc metal positive electrode or a zinc alloy positive electrode.

[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0026] Excellent low-temperature antifreeze performance: The biomimetic osmotic pressure regulator, namely the biologically derived natural antifreeze small molecule regulator, contains abundant polar groups (such as hydroxyl, amino, etc.), which can form strong hydrogen bond interactions with water molecules, breaking the original hydrogen bond network in pure water, significantly reducing the activity of free water, inhibiting the nucleation and growth of large-sized ice crystals, so that the electrolyte maintains extremely high ionic conductivity at -20℃ or even lower temperatures.

[0027] Highly efficient negative electrode interface protection: Biomimetic osmotic pressure regulators can participate in Zn 2+ The solvation layer replaces part of the bound water, reducing the direct reduction of water molecules; at the same time, the biomimetic osmotic pressure regulator can form a dense dynamic adsorption protective layer on the zinc anode surface, homogenize the interfacial electric field distribution, fundamentally inhibit the aqueous hydrogen evolution reaction (HER) and achieve dendrite-free smooth deposition of zinc.

[0028] Significantly suppresses the shuttle effect of polyiodide in the positive electrode: For iodine-based composite positive electrodes, the abundant functional groups in the biomimetic osmotic pressure regulator can interact with intermediate polyiodide ions (such as I) generated during charging and discharging. 3- It forms strong hydrogen bonds or coordination, effectively "anchoring" it to the positive electrode region, blocking its diffusion and shuttle to the negative electrode, thereby greatly improving the coulombic efficiency of the zinc-iodine battery and reducing its self-discharge rate.

[0029] All-environmental adaptability and long lifespan: Combining the above-mentioned bidirectional regulation effect on the positive and negative electrodes, the zinc-iodine battery assembled with the antifreeze electrolyte of this invention not only has an ultra-long cycle life at room temperature, but also exhibits excellent capacity retention and rate performance in extremely cold environments, greatly expanding the practical application boundaries of aqueous zinc-iodine batteries. Attached Figure Description

[0030] Figure 1 The diagram shows the state of zinc sulfate solution with different volume percentages of glycerol added and left at -20°C for 24 hours.

[0031] Figure 2 It is the differential scanning calorimetry (DSC) test curve of the electrolyte;

[0032] Figure 3 It is an infrared (FT-IR) spectral analysis of the electrolyte solvation structure;

[0033] Figure 4 It is a Raman spectral analysis of the solvation structure of the electrolyte;

[0034] Figure 5 The copper-zinc half-cell assembled at -20°C using the electrolyte from Example 1 operates at a current density of 0.5 mA / cm². 2 Coulomb efficiency;

[0035] Figure 6 It is a zinc-zinc symmetric cell assembled with electrolyte at a current density of 1 mA / cm². 2 Long-cycle testing at -20℃;

[0036] Figure 7 In Example 5, a zinc-zinc symmetric cell was used at a current density of 0.5 mA / cm². 2 Long-cycle testing at -30℃;

[0037] Figure 8 This is an in-situ observation of the zinc deposition process in ZSO (left) and ZSO+30%GL (right) electrolytes. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them.

[0039] Unless otherwise specified, all chemical reagents, active materials, and raw materials used in this invention can be purchased through legitimate commercial channels and can be used directly without further purification. Specifically, the zinc salts involved (including but not limited to zinc sulfate, zinc perchlorate, zinc acetate, zinc trifluoromethanesulfonate, etc.), bio-derived natural antifreeze small molecule regulators (including but not limited to glycerol, sorbitol, mannitol, trehalose, glucose, sucrose, fructose, proline, alanine, betaine, trimethylamine oxide, sarcosine, aspartic acid, serine, valine, leucine, isoleucine, glutamine, urea, etc.), and elemental iodine, conductive carbon black, binders, etc., used in the positive electrode, are all commercially available analytical grade (AR grade) or battery-grade reagents.

[0040] Example 1

[0041] Step S1: Weigh zinc sulfate heptahydrate and dissolve it in deionized water to prepare a ZnSO4 solution with a molar concentration of 2 mol / L.

[0042] Step S2: Measure out a ZnSO4 solution and slowly add glycerol under stirring at room temperature, wherein the volume ratio of glycerol in the solution is 30%, and continue stirring for 1 hour to obtain a uniform and transparent electrolyte.

[0043] Step S3, Battery Assembly: Zinc-Zinc Symmetrical Battery: Using zinc sheets as positive / negative electrodes, glass fiber as the separator, and electrolyte injected. Stainless Steel Symmetrical Battery: Using stainless steel gaskets as positive / negative electrodes, glass fiber as the separator, and electrolyte injected. Zinc-Iodine Full Battery: Assembling a coin cell with an iodine positive electrode (iodine@activated carbon:conductive carbon black:PVDF=8:1:1) and a zinc sheet as the negative electrode.

[0044] Step S4, Performance Testing: The electrolyte exhibits a conductivity of 4.38 mS / cm at -20℃. When applied to a zinc-zinc symmetric battery at a low temperature of -20℃, the electrolyte showed a conductivity of 1 mAh / cm². -2 Stable cycling for over 2000 hours. The coulombic efficiency of the Zn / / Cu half-cell was 98.46% at -20℃. At 25℃, the ionic conductivity of the electrolyte was 12.8 mS / cm, and the zinc-zinc symmetric cell could cycle stably for over 3000 hours at room temperature.

[0045] Comparative Example 1

[0046] Step S1: Weigh zinc sulfate heptahydrate and dissolve it in deionized water to prepare a ZnSO4 solution with a molar concentration of 2 mol / L.

[0047] Step S2, without adding any biomimetic regulators, serves as a baseline control, directly demonstrating the lack of antifreeze and interface instability in the "no additive" state.

[0048] In step S3, at a low temperature of -20°C, the electrolyte exhibited significant freezing and solidification, leading to a surge in battery internal resistance and a conductivity test result of 0.83 mS / cm. Normal charge-discharge cycles were impossible at -20°C. In contrast, the electrolytes of Examples 1 and 5 maintained excellent fluidity at low temperatures, demonstrating the crucial role of bio-derived natural antifreeze small molecule regulators in reconstructing the hydrogen bond network to lower the freezing point. Observing the in-situ deposition process of the electrolytes of Comparative Example 1 and Example 1 under the same conditions revealed that zinc dendrites grew rapidly on the zinc sheet in the electrolyte of Comparative Example 1, while the electrolyte of Example 1 effectively suppressed zinc dendrite growth, resulting in a longer cycle life for the zinc-zinc symmetric battery.

[0049] Example 2

[0050] In this embodiment, the specific preparation steps of the modified aqueous electrolyte are as follows:

[0051] Step S1: Weigh a predetermined mass of zinc sulfate heptahydrate solid and dissolve it in deionized water. Stir magnetically until completely dissolved to prepare a zinc sulfate basic aqueous solution with a molar concentration of 2 mol / L.

[0052] Step S2: Measure out zinc sulfate basic aqueous solution and glycerol respectively, mix them at a volume ratio of 7:3, and continuously stir magnetically at room temperature until the bulk phase is highly homogeneous to obtain a water / glycerol mixture with a glycerol volume ratio of 30%.

[0053] Step S3: Weigh the total mass of the water / glycerol mixture, and based on this total mass, weigh L-proline powder at a mass fraction of 10 wt% and add it to the water / glycerol mixture;

[0054] Step S4: Continuously stir with magnetic force at room temperature until the L-proline powder is completely dissolved, and finally obtain a deep eutectic aqueous electrolyte with high chemical homogeneity and clear transparency.

[0055] Example 3

[0056] Step S1: Weigh an appropriate amount of deionized water as the matrix solvent, add zinc trifluoromethanesulfonate solid to it, and stir continuously until it is completely dissolved to prepare a basic aqueous solution of zinc trifluoromethanesulfonate with a molar concentration of 1 mol / L.

[0057] Step S2: Add natural biological antifreeze small molecule betaine powder to the above zinc trifluoromethanesulfonate-based aqueous solution at a mass percentage of 20 wt%. Stir continuously with a magnetic stirrer at room temperature (25°C) until the solid particles are completely dissolved to obtain a clear, transparent, and precipitate-free deep eutectic aqueous electrolyte.

[0058] Example 4

[0059] Step S1: First, zinc sulfate heptahydrate solid was dissolved in deionized water to prepare a zinc sulfate basic aqueous solution with a molar concentration of 2 mol / L. Then, the zinc sulfate basic aqueous solution and glycerol were mixed in bulk at a volume ratio of 7:3 and magnetically stirred until homogeneous to obtain a water / glycerol mixture with a glycerol volume percentage of 30%. Next, multiple water / glycerol mixtures of the same mass were weighed as a base, and based on the total mass of each water / glycerol mixture, L-proline powder was added exogenously to each water / glycerol mixture at 0 wt%, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, and 80 wt%, respectively. The mixture was continuously magnetically stirred at room temperature until the solid powder was completely dissolved to obtain a series of electrolyte samples with different L-proline mass fractions.

[0060] Step S2: The gradient series electrolyte samples prepared in Step S1 were simultaneously placed in an ultra-low temperature environment of -30℃ and frozen for more than 12 hours. The macroscopic physical state of each group of samples was then observed and recorded. The physical state assessment results showed that the electrolyte samples with an L-proline mass fraction of 0 wt% all solidified and froze at -30℃; while the electrolyte samples with L-proline mass fractions of 10 wt% to 80 wt% remained in a fluid state at -30℃, and no ice crystals or solid salt precipitation were observed.

[0061] Step S3: Using the aforementioned gradient series of electrolyte samples, a glass fiber separator was impregnated to assemble a stainless steel / stainless steel (SS / / SS) symmetric battery. The battery was equilibrated at -30℃ for 6 hours, and its ultra-low temperature ionic conductivity was measured and calculated using electrochemical impedance spectroscopy (EIS). The test results showed that with the increase of L-proline mass fraction, the ionic conductivity of the electrolyte at -30℃ first increased and then decreased. Among them, when the L-proline addition was 10wt%, the electrolyte exhibited the highest ultra-low temperature ionic conductivity while maintaining non-freezing at -30℃. Therefore, in this embodiment, 10wt% L-proline was determined as the optimal addition amount, ultimately obtaining a clear and transparent deep eutectic aqueous electrolyte.

[0062] Example 5

[0063] Step S1: Weigh a predetermined mass of zinc sulfate heptahydrate solid and completely dissolve it in deionized water. Stir magnetically until completely dissolved to prepare a zinc sulfate basic aqueous solution with a molar concentration of 2 mol / L.

[0064] Step S2: Measure zinc sulfate basic aqueous solution and glycerol, mix them in bulk at a volume ratio of 7:3, and continuously stir magnetically at room temperature until highly homogeneous to obtain a water / glycerol mixture with a glycerol volume ratio of 30%.

[0065] Step S3: With the concentration of the zinc sulfate base aqueous solution fixed at 2 mol / L and the glycerol volume percentage at 30%, urea was added to the water / glycerol mixture, and the urea mass fraction was varied (0 wt%~80 wt%) for comparative analysis. The results showed that when the urea mass fraction exceeded 10 wt%, the system viscosity became too high, leading to a significant decrease in ionic conductivity; when the urea mass fraction was below 10 wt%, it was unable to effectively inhibit electrolyte freezing at -30℃. Therefore, 30 vol% glycerol + 10 wt% urea was determined to be the optimal synergistic ratio.

[0066] Step S4: Under an ultra-low temperature environment of -30℃, the electrolyte (10wt% urea group) in this embodiment is clear in appearance, has good fluidity, and exhibits no solid ice crystal precipitation. Its ultra-low temperature ionic conductivity reaches as high as 2.51 mS / cm, the highest among all gradient groups. The zinc / zinc (Zn / / Zn) symmetric battery assembled with this electrolyte operates at a current density of 0.5 mA / cm². -2 The charge / discharge capacity is 0.5mAh / cm³. -2 Under these conditions, long-term stable operation was achieved. The in-situ combination of glycerol and urea to construct a deep eutectic solvent microenvironment significantly reduced the freezing point of the solution, achieving a dual breakthrough in bulk ion mass transfer and interfacial stability at -30℃.

[0067] Example 6

[0068] Step S1: Weigh a predetermined mass of zinc perchlorate solid and completely dissolve it in deionized water. Stir magnetically until completely dissolved to prepare a basic aqueous solution of zinc perchlorate with a molar concentration of 2 mol / L.

[0069] Step S2: Measure the zinc perchlorate basic aqueous solution and glycerol, mix them in bulk at a volume ratio of 7:3, and continuously stir magnetically at room temperature until highly homogeneous to obtain a water / glycerol mixture with a glycerol volume ratio of 30%.

[0070] Step S3: Weigh the total mass of the water / glycerol mixture, and based on this total mass, weigh the natural biological antifreeze small molecule betaine powder at a mass fraction of 10wt%, and add it exogenously to the water / glycerol mixture;

[0071] Step S4: At room temperature (25±5℃), the mixture is continuously magnetically stirred for 1 hour to promote the formation of a strong hydrogen bond synergistic network between the inorganic salt, co-solvent (glycerol), and zwitterionic additive (betaine) until the betaine powder is completely dissolved, and finally a clear and transparent modified aqueous electrolyte is obtained.

[0072] The foregoing has shown and described the basic principles, main features and advantages of the present invention. Various changes and modifications can be made to the present invention without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of the present invention as claimed.

Claims

1. A biomimetic osmotic pressure-regulated aqueous antifreeze electrolyte for zinc-ion batteries, characterized in that: The antifreeze electrolyte comprises zinc salt, water, and a bio-derived natural antifreeze small molecule regulator. This bio-derived natural antifreeze small molecule regulator is selected from biocompatible small molecules with multiple hydrophilic groups, specifically from at least one of polyols, sugars, amino acids and their derivatives, betaines, or amides. The antifreeze electrolyte is used to assemble an aqueous zinc-ion battery suitable for low-temperature environments. The bio-derived natural antifreeze small molecule regulator acts as a hydrogen bond donor and acceptor, constructing a biomimetic solvation system with deep eutectic properties, disrupting the hydrogen bond network between water molecules, and significantly reducing the electrolyte's freezing point. The bio-derived natural antifreeze small molecule regulator contains abundant polar groups that can form strong hydrogen bond interactions with water molecules, breaking the original hydrogen bond network in pure water, significantly reducing the activity of free water, and inhibiting the nucleation and growth of large-sized ice crystals. This allows the electrolyte to maintain extremely high ionic conductivity even at low temperatures, effectively inhibiting the growth of zinc anode dendrites and hydrogen evolution side reactions, significantly improving the battery's cycle stability and coulombic efficiency, thereby achieving long-term stable cycling of the aqueous zinc-ion battery in low-temperature environments.

2. The biomimetic osmotic pressure-regulated aqueous zinc-ion battery antifreeze electrolyte according to claim 1, characterized in that... The bio-derived natural antifreeze small molecule regulator is specifically selected from at least one of the following categories: Polyols: at least one of glycerol, sorbitol or mannitol; Sugars: at least one of trehalose, glucose, sucrose or fructose; Amino acids and their derivatives: at least one of proline, alanine, aspartic acid, serine, valine, leucine, isoleucine, glutamine, or sarcosine; Betaines: at least one of betaine or trimethylamine oxide; Amides: Urea.

3. The biomimetic osmotic pressure-regulated aqueous zinc-ion battery antifreeze electrolyte according to claim 1, characterized in that: The bio-derived natural antifreeze small molecule regulator has a mass percentage of 5% to 80% in the antifreeze electrolyte.

4. The biomimetic osmotic pressure-regulated aqueous zinc-ion battery antifreeze electrolyte according to claim 1, characterized in that: The zinc salt is selected from at least one of zinc sulfate, zinc chloride, zinc acetate, zinc trifluoromethanesulfonate, or zinc perchlorate, and the molar concentration of the zinc salt in the antifreeze electrolyte is 0.5~4 mol / L.

5. The biomimetic osmotic pressure-regulated aqueous zinc-ion battery antifreeze electrolyte according to claim 1, characterized in that: The bio-derived natural antifreeze small molecule regulator is composed of polyols with different functional orientations, amino acids and their derivatives, and / or amides. Through multi-site synergistic effects between different polar functional groups, it can further enhance the perturbation depth of the hydrogen bond network of bulk water molecules while maintaining high ionic conductivity, and construct a more flexible dynamic adsorption protective layer at the solid-liquid interface. By using polyols and amino acids and their derivatives, and / or amides to modify the aqueous electrolyte, the excellent low-temperature antifreeze properties of polyols can be organically combined with the strong chemical anchoring of polyiodides and the regulation of zinc nucleation behavior by amino acids and their derivatives, and / or amides, thereby synergistically improving the electrochemical performance of the battery.

6. An aqueous zinc-ion battery, characterized in that: The aqueous zinc-ion battery includes a positive electrode, a negative electrode, a separator, and the biomimetic osmotic pressure regulating aqueous zinc-ion battery antifreeze electrolyte as described in any one of claims 1 to 5.

7. The aqueous zinc-ion battery according to claim 6, characterized in that: The aqueous zinc-ion battery is a zinc-iodine battery, wherein the negative electrode is a zinc metal negative electrode or a zinc alloy negative electrode, the separator is a glass fiber separator, a cellulose separator or a polymer separator, and the positive electrode is an iodine-based composite positive electrode, which includes a conductive carbon host carrier and an active material loaded in the conductive carbon host carrier, wherein the active material is selected from at least one of elemental iodine or iodides.

8. The aqueous zinc-ion battery according to claim 7, characterized in that: The conductive carbon host carrier is selected from at least one of porous carbon, carbon nanotubes, graphene, carbon fiber cloth, MXene, or conductive polymers; the active substance is stably adsorbed in the conductive carbon host carrier by at least one of physical confinement, chemical coordination anchoring, or electrostatic attraction.

9. The aqueous zinc-ion battery according to claim 6, characterized in that: The aqueous zinc-ion battery is a zinc-zinc battery, wherein the negative electrode is a zinc metal negative electrode or a zinc alloy negative electrode, the separator is a glass fiber separator, a cellulose separator or a polymer separator, and the positive electrode is a zinc metal positive electrode or a zinc alloy positive electrode.

10. The aqueous zinc-ion battery according to claim 6, characterized in that: The aqueous zinc-ion battery is a stainless steel battery, wherein the negative electrode is a stainless steel negative electrode, the separator is a glass fiber separator, a cellulose separator or a polymer separator, and the positive electrode is a stainless steel positive electrode.

Citation Information

Patent Citations

  • Electrolyte taking sodium pyruvate as additive and application of electrolyte in zinc battery

    CN121839921A

  • Aqueous zinc ion battery electrolyte containing 1, 3-dihydroxyacetone as well as preparation method and application of aqueous zinc ion battery electrolyte

    CN121862903A

  • Aqueous zinc battery electrolyte, preparation method and application thereof

    CN122025857A

  • Water-based zinc ion battery modified electrolyte and preparation method thereof

    CN122136494A